Solusi Filsafat Jiwa Sadra Pada Problem Paradoks dan Implikasi Onto-Epistemik Transhumanisme Nick Bostrom - Fadhlu Rahman (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2022)
This study aims to examine and provide a solution to Nick Bostrom's onto-epistemic theoretical consistency problem of transhumanism which is considered to have a conceptual paradox and its implications for the basic concepts of transhumanism which consists of three pillars, namely: superintelligence, superlongevity, and super wellbeing. The testing and solutions that will be given are carried out through one of the major themes of the discourse on the relation of soul and body and the process of perfection in the tradition of Islamic philosophy. One form of mature philosophical discourse is in the Sadra’s philosophy of Soul. Therefore, the writer wants to describe the ontological and epistemological foundations of Bostrom's transhumanism as well as the Sadra’s philosophy of soul, and look at the paradoxes and onto-epistemic implications of the three pillars of transhumanism based on Sadra's view by descriptive and comparative analysis methods. In previous studies on the issue of transhumanism and the philosophy of the soul, Sadra still only focused on the description of each of these two issues. In addition, the study of this issue (transhumanism) focuses on the problem of its metaphysical basis by a western philosophical approach, so, this study wants to analyze it from the perspective of Islamic philosophy which is considered authoritative as the basis for studying metaphysical issues in the onto-epistemic context of transhumanism. I find that his onto-epistemic assumptions include; first, its dualism of epiphenomenalism as the basis of ontology necessitates the impossibility of matter having direct access to immaterial states of the self, while its limitations cannot create the perfection that Bostrom intended; and the second, his scientism as the basis of his epistemology require perfection that is not comprehensive and holistic, from the results of the analysis, I assesses that Bostrom's metaphysical assumptions are problematic both in terms of coherence and correspondence on the pillars of his transhumanism, and Sadra’s philosophical thought provides a solution in the form of the onto-epistemic basis for his soul philosophy and the process of perfecting in the problem of the fragility of Bostrom's Transhumanism ideas which can then provide the ideal form of the perfect human that Bostrom assumes.